2021
DOI: 10.1016/j.scitotenv.2020.142901
|View full text |Cite
|
Sign up to set email alerts
|

Stable-isotopic and metagenomic analyses reveal metabolic and microbial link of aerobic methane oxidation coupled to denitrification at different O2 levels

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…Hyphomicrobium spp. were also detected in other studies investigating methane oxidation coupled to denitrification (Costa et al, 2000; Ma et al, 2020) and methane biofilters (López et al, 2018). In previous studies, it was hypothesized that Hyphomicrobium spp.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Hyphomicrobium spp. were also detected in other studies investigating methane oxidation coupled to denitrification (Costa et al, 2000; Ma et al, 2020) and methane biofilters (López et al, 2018). In previous studies, it was hypothesized that Hyphomicrobium spp.…”
Section: Discussionsupporting
confidence: 74%
“…are type II methanotrophs and Methylocystis spp. or closely related bacteria were reported in other studies investigating aerobic methane oxidation coupled with denitrification (Beck et al, 2013; Lee et al, 2019; Ma et al, 2020) and the biofiltration of methane (La et al, 2018; López et al, 2018). Beck et al (2013) found that Methylocystaceae (Family of Methylocystis ) increased in abundance in response to methane in aerobic microcosm incubations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The ultra-micro size of Polynucleobacter is probably the cause for its high abundance with respect to the total quantity of microbes. Hyphomicrobium, Methylotenera, and Methyloversatilis were known as major players in aerobic denitrification systems that were supplied with methanol as a carbon source. Hyphomicrobium was also reported as the manganese oxidizing bacteria that was found in a biofilter developed for Fe, Mn, and As­(III) removal and identified as the main microbe responsible for Fe and Mn-oxidation in a slow sand filter . Therefore it showed a relatively high abundance in iron-modified systems.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, BDPs are more expensive, 6,21 and methane is susceptible to oxygen concentrations. 22 Although natural cellulose-based sources have been studied as potential alternatives, 23 the initial and saturated carbon release rates vary signicantly, and the effect aer addition is unstable, making them unsuitable for widespread application. 24 Therefore, a lowcost, high-performance, and environmentally friendly external carbon source is necessary.…”
Section: Introductionmentioning
confidence: 99%